2022
DOI: 10.1098/rsos.211171
|View full text |Cite
|
Sign up to set email alerts
|

Quantity over quality? Prey-field characteristics influence the foraging decisions of little penguins ( Eudyptula minor )

Abstract: Quantifying prey characteristics is important for understanding the foraging behaviour of predators, which ultimately influence the structure and function of entire ecosystems. However, information available on prey is often at magnitudes which cannot be used to infer the fine-scale behaviour of predators, especially so in marine environments where direct observation of predator–prey interactions is rarely possible. In the present study, animal-borne video data loggers were used to determine the influence of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The foraging distances observed in our study are consistent with former studies on the fine‐scale spatial use of lactating females demonstrating very restricted foraging area (Larue et al., 2019 ). Presence of pups may limit females' foraging trip distance, as observed in other marine species such as little penguin (Sutton & Arnould, 2022 ).…”
Section: Discussionmentioning
confidence: 97%
“…The foraging distances observed in our study are consistent with former studies on the fine‐scale spatial use of lactating females demonstrating very restricted foraging area (Larue et al., 2019 ). Presence of pups may limit females' foraging trip distance, as observed in other marine species such as little penguin (Sutton & Arnould, 2022 ).…”
Section: Discussionmentioning
confidence: 97%
“…The swimming speed of a juvenile baitfish is approximately one tenth that of an adult fish [ 13 ] and, thus, it is possible that little penguins prefer targeting juvenile fish, finding them easier to capture. Indeed, a recent study demonstrated that little penguins spent longer periods at patches of juvenile prey [ 35 ]. While this prey type may be of lower energetic value, it may make for an efficient meal as it occurs in large schools and has shorter handling times in comparison to other prey.…”
Section: Discussionmentioning
confidence: 99%
“…However, its short chase and handling duration, and schooling nature, would mean its capture rate could be comparatively high, allowing individuals to rapidly exploit prey patches. Indeed, the prominence of bellowsfish in the present study would suggest that little penguins may rely on these fish as an important prey item, given their high capture rate and abundance [ 35 ]. By contrast, while the estimated gross energy gain from jellyfish was also relatively low, their longer handling time (possibly due to their larger size) contributed to their low energetic profitability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis showed that hunting time decreased with warmer waters, especially during the Guard and Post Guard stages (min-max SST 12-18.4 ºC). During the breeding season, little penguins can switch foraging strategy, requiring different hunting time, and targeting different types of prey and prey aggregations with varying energetic content (Cavallo et al 2020;Sutton & Arnould 2022). More dispersed and/or less abundant prey in colder and less-stratified waters, or increased prey availability in warmer and stratified waters (Meyer et al 2020) can lead to changes in effort allocated to hunting activities.…”
Section: )mentioning
confidence: 99%